(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Recently, the Middle Benue Trough has become an area of interest in the country for the exploration activities in Ebenyi-A well which will give more insights into the subsurface potentials in the area. Several authors studied the Awgu Formation geologically, stratigraphically, petrographically, and geochemically but the petrographical and geochemical studies on the carbonate deposits to evaluate the potential reservoir quality are scarce in the literature. This study focuses on the geology, field investigation, petro-sedimentological and geochemical studies. The field investigation reveals two lithofacies of the carbonate reservoir rock namely shelly and crystalline carbonate facies. Petrographic studies show that the shelly facies are characterized by high diversity brachiopod, gastropods, shell fragments, alga materials, high CaO, and classified as biosparite on the Folk classification and wackestone/packstone to crystalline facies on the Dunham classification. Pore types in the shelly biosparmicrite microfacies are moldic porosity while the crystalline micritic microfacies is distinguished by an increased composition of grains which enhance grain-to-grain contacts and promoting interparticle porosity. The geochemical results show that the carbonates of Awgu Formation were deposited under a shallow marine environment. It also indicates that the MgO values are lower than the CaO values. The diagenetic processes considered are micritization and neomorphism. The outcome of these investigations will contribute to understanding of carbonate pore types dissolution in the deposits that will enhance identification of variable reservoir hydraulic flow units within the carbonate lithofacies for successful exploration in the Middle Benue Trough.